Sistemny podkhod v otsenke statokineticheskoi funktsii u sportsmenov - Sidorova, O. P. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
The author of this study tries to substantiate scientifically the diagnosis of all main systems of athlete's organism by motor reactions of nystagmus fixation. Statokinetic system consists of proprioreceptors, photoreceptors of retina, and tactile receptors. All of them provide statokinetic stability, or, by the other words, the ability of these analyzators to hold on the body's balancing and space orientation during active and passive movements. Statokinetical functioning reflects more adequately the body resistance to irritants impact arising during moving. The latter makes this kind of analysis very useful for sports activities, especially for athlete's functional states diagnosis.